Peran Teman Sepermainan dalam Membentuk Sikap Pemuda Pedesaan terhadap Pekerjaan di Sektor Pertanian Padi (Kasus Pemuda di Desa Ciasmara, Kecamatan Pamijahan Kabupaten Bogor) - Nugraha, Yogaprasta Adi; Supriatna, Raden Atang (Department of Agribusiness, Halu Oleo University, 2020)
The agricultural sector is holding a pivotal position to national income but however, the importance of the agricultural sector is not supported by the regeneration of agriculture workers. The number of agricultural workers continuously decreasing during a time, in order to understand these phenomena there is a number of factors that have led to a decline in youth participation in the agriculture sector, yet there is only limited research that is trying to determine the relationship between socialization agent and working preference. This study has several objectives, among others: (1) Identifying youth interactions with peer-group in the agricultural sector. (2) Identifying youth attitudes towards agriculture work (3) Analyzing the correlation between interactions with friends in the agricultural sector with youth attitudes towards agriculture work. This research uses a quantitative method with a descriptive - correlational approach and was taken place in Ciasmara Village, Pamijahan District, Bogor Regency from March 2019 until Juli 2019. A total of 129 youth were selected as research respondents in this study. This study found that parents and peers have important positions in making youth interested in working in the agricultural sector. The two primary socialization agents were able to influence youth with different approaches. Parents through work-involvement as family labor meanwhile, the peer-groups through doing activities together in farmland.